A Relational Account of Call-by-Value Sequentiality - Riecke, Jon G.; Sandholm, Anders B. (BRICS Report Series, 1997)
We construct a model for FPC, a purely functional, sequential, call-by-value language. The model is built from partial continuous functions, in the style of Plotkin, further constrained to be uniform with respect to a class of logical relations. We prove that the model is fully abstract.